The Muscle Activation Differences in Post-Stroke Upper Limb Flexion Synergy Based on Spinal Cord Segments: A Preliminary Proof-of-Concept Study - Liu, Gang; Chia, Chin-hsuan; Wang, Wei-ning; Cao, Yue; Tian, Shan; Shen, Xue-yan; Chen, Ying; Lu, Rong-rong; Wu, Jun-fa; Zhu, Yu-lian; Wu, Yi (Frontiers in Neurology, 2021)
Objective: To study the activation difference of muscles innervated by cervical cord 5-6 (C5-C6) and cervical cord 8- thoracic cord 1 (C8-T1) in upper limb flexion synergy after stroke. Methods: Surface electromyography (sEMG) signals were collected during elbow flexion in stroke patients and healthy controls. The normalized activation of two pairs of muscles that could cause similar joint movement but dominated by different spinal cord segments were compared (clavicular part of pectoralis major, PC vs Sternocostal part of pectoralis major, PS; Flexor carpi radialis, FCR vs Flexor carpi ulnaris, FCU). In each muscle pair, one muscle is innervated by the same spinal cord segment (C5-C6) dominating the elbow flexion and the other is not. The comparison of the activation of the same muscle between patients and healthy controls were proceeded after the standardization based on the activation of the biceps brachii in elbow flexion. Results: There was no difference between the PC and PS’s normalized activation in health controls while the PC’s normalized activation was higher than PS in stroke patients during elbow flexion. Similarly, there was no significant difference in normalized activation between FCR and FCU in healthy controls, and the same is true for stroke patients. However, the standardized activation of both FCR and FCU in stroke patients was significantly lower than that in healthy controls. Conclusion: After stroke, the activation of the distal muscles of the upper limb decreased significantly regardless of the difference of spinal cord segments; while the activation of the proximal muscles innervated by the same spinal cord segment (C5-C6) dominating the elbow flexion showed higher activation during flexion synergy. The difference in muscle activation based on spinal cord segments may be the reason for the stereotyped joint movement of upper limb flexion synergy.